IMPLEMENTASI BIMBINGAN KONSELING DALAM MENANGANI PROBLEMATIKA AKHLAK PESERTA DIDIK DI MTsN 15 JOMBANG - Mahmudah; Sholihul Anshori (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the implementation of guidance and counseling services, identify students' moral problems, and explain how guidance and counseling was implemented to address these problems at MTsN 15 Jombang. The research employed a descriptive qualitative approach using interviews, observations, and documentation as data collection techniques. Data validity was strengthened through source, technique, and time triangulation. The findings show that guidance and counseling services were implemented through individual counseling, group counseling, direct advice, character building, and collaboration with homeroom teachers and Islamic Education teachers. The students' moral problems included low discipline, impolite behavior toward teachers and peers, violations of school rules, and weak awareness of moral values in daily life. These problems were influenced by peer environment, family conditions, and low self-control. The implementation of guidance and counseling involved personal approaches, motivation, religious coaching, and coordinated school support. The study confirms that guidance and counseling plays a strategic role in strengthening students' moral character when implemented systematically, educationally, and continuously.